2
$\begingroup$

This is something I've been thinking about lately;

$$\int_0^1 \int_0^1 \frac{1}{1-(xy)^2} dydx$$ Solutions I've read involve making the substitutions: $x= \frac{sin(u)}{cos(v)}$ and $y= \frac{sin(v)}{cos(u)}$. This reduces the integral to the area of a right triangle with both legs of length $\frac{\pi}{2}$. My problem is that coming up with this substitution is not at all obvious to me, and realizing how the substitution distorts the unit square into a right triangle seems to require a lot of reflection. My approach without fancy tricks involves letting $u = xy$ and then the integral "simplifies" accordingly:

$\begin{align*} \int_0^1 \int_0^1 \frac{1}{1-(xy)^2} dydx &= \int_0^1\frac{1}{x}\int_0^x \frac{1}{1-u^2}dudx\\ &= \int_0^1\frac{1}{2x}\int_0^x \frac{1}{1-u}+\frac{1}{1+u}dudx\\ &= \int_0^1\frac{1}{2x}ln\left(\frac{1+x}{1-x}\right)dx \end{align*}$

If I've done everything right this should be $\frac{\pi^2}{8}$ but I haven't figured out how to solve it.

$\endgroup$
2
$\begingroup$

You can also do this, and this one does not involve any fancy tricks:

Consider the double integral: $$I=\int_{0}^{\infty}\int_{0}^{\infty}\frac{1}{(1+x)(x+y^2)}dydx.$$

Integrate with respect to $y$ first and recognize this is :

$$I=\int_{0}^{\infty} \frac{1}{1+x}\lim_{y \rightarrow \infty} \frac{\arctan{\frac{y}{\sqrt{x}}}}{\sqrt {x}} dx=\int_{0}^{\infty}\frac{\frac{\pi}{2}}{\sqrt{x}{(1+x)}}dx.$$ Now if you apply the transformation $u=\sqrt{x}, du=\frac{1}{2\sqrt{x}}dx,$ you get $$I=\int_{0}^{\infty} \frac{\pi}{(1+u^2)}du=\frac{\pi^2}{2}.$$

On the other hand, reverse the order of integration in $I$ as such: $$I=\int_{0}^{\infty}\int_{0}^{\infty}\frac{1}{(1+x)(x+y^2)}dxdy.$$ Now integrate with respect to $x$ using partial fractions as such:

$$\frac{1}{(1+x)(x+y^2)}=\frac{1}{y^2-1} \left(\frac{1}{1+x}-\frac{1}{x+y^2}\right).$$

$$I=\int_{0}^{\infty}\int_{0}^{\infty}\frac{1}{y^2-1} \left(\frac{1}{1+x}-\frac{1}{x+y^2}\right)dxdy=\int_{0}^{\infty}\lim_{x\rightarrow \infty}\frac{\ln(1+x)-\ln(x+y^2)}{y^2-1}dy=\int_{0}^{\infty}\frac{\ln(y^2)}{y^2-1}dy=\int_{0}^{\infty}\frac{2\ln(y)}{y^2-1}dy.$$

Now consider $$J=\int_{0}^{1}\frac{\ln(y)}{y^2-1}dy.$$ A u-substitution $y=\frac{1}{z}, dy=\frac{-1}{z^2} dz$ tells us: $$J=\int_{1}^{\infty}\frac{\ln(z)}{z^2-1}dz.$$ This tells us: $$J=\frac{I}{4}=\frac{\pi^2}{8}.$$ Now let us make the substitution $z=\frac{1-t}{1+t}, dz=\frac{-2}{(t+1)^2}dt.$ We have:

$$J=\frac{\pi^2}{8}=\int_{0}^{1} \frac{\ln(1+t)-\ln(1-t)}{2t} dt,$$ the integral you arrived at.

$\endgroup$
5
$\begingroup$

Here is an alternative derivation. The form of the integrand suggest expanding it a geometrical series $$\frac{1}{1-(xy)^2} = \sum_{n=0}^\infty x^{2n}y^{2n}$$ Now integrating term by term we get $$\int_0^1\int_0^1\frac{{\rm d}x{\rm d}y}{1-(xy)^2} = \sum_{n=0}^\infty \frac{1}{(2n+1)^2}$$ and from the well known result $\frac{\pi^2}{6} = \sum_{n=1}^\infty \frac{1}{n^2} = \sum_{n=0}^\infty\frac{1}{(2n+1)^2} + \sum_{n=1}^\infty\frac{1}{(2n)^2}$ we get $$\int_0^1\int_0^1\frac{{\rm d}x{\rm d}y}{1-(xy)^2} = \frac{\pi^2}{8}$$

$\endgroup$
  • $\begingroup$ It's actually interesting, I found this integral by learning about ways to prove the well known result. So, while the answer is insightful, it's not very useful to me. I probably should have posted that in the question. $\endgroup$ – Lee Fisher Dec 23 '15 at 13:15
  • 1
    $\begingroup$ @LeeFisher This answer might be of interest then. $\endgroup$ – Winther Dec 23 '15 at 13:30
2
$\begingroup$

If you haven't an idea, just start:

$$\int_{0}^{1}\int_{0}^{1}\frac{1}{1-(xy)^2}\space\text{d}y\text{d}x=$$ $$\int_{0}^{1}\left[\int_{0}^{1}\frac{1}{1-(xy)^2}\space\text{d}y\right]\text{d}x=$$


For the integrand $u=xy$ and $\text{d}u=x\space\text{d}y$.

This gives a new lower bound $u=x\cdot0=0$ and upper bound $u=x\cdot1=x$:


$$\int_{0}^{1}\left[\frac{1}{x}\int_{0}^{x}\frac{1}{1-u^2}\space\text{d}u\right]\text{d}x=$$ $$\int_{0}^{1}\left[\frac{1}{x}\left[\tanh^{-1}\left(u\right)\right]_{0}^{x}\right]\text{d}x=$$ $$\int_{0}^{1}\left[\frac{1}{x}\left(\tanh^{-1}\left(x\right)-\tanh^{-1}\left(0\right)\right)\right]\text{d}x=$$ $$\int_{0}^{1}\left[\frac{1}{x}\left(\tanh^{-1}\left(x\right)-0\right)\right]\text{d}x=$$ $$\int_{0}^{1}\left[\frac{\tanh^{-1}\left(x\right)}{x}\right]\text{d}x=$$ $$\frac{1}{2}\left[\text{Li}_2(x)-\text{Li}_2(-x)\right]_{0}^{1}=$$ $$\frac{1}{2}\left(\left(\text{Li}_2(1)-\text{Li}_2(-1)\right)-\left(\text{Li}_2(0)-\text{Li}_2(-0)\right)\right)=$$ $$\frac{1}{2}\left(\frac{\pi^2}{4}-0\right)=$$ $$\frac{1}{2}\left(\frac{\pi^2}{4}\right)=\frac{\pi^2}{8}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.